Implementasi Wakaf Profesi dalam Perspektif Maqasid al-Syariah: Studi Kasus di Pondok Modern Darussalam Gontor Putri - Imam Kamaluddin; Eko Nur Cahyo; Khurun’in Zahro’; Mizan Sul Amalia Latjuba (Jurnal Ilmiah Ekonomi Islam, 2025)
This study aims to analyze the implementation of professional waqf at Pondok Modern Darussalam Gontor for Girl from the perspective of Maqasid al-Syariah. Professional waqf is understood as a form of empowerment of individual skills potential that are donated for the benefit of education, da'wah, and community development. This study seeks to explore how the principles of Islamic law and the objectives of sharia (maqasid), especially hifz al-'aql, hifz al-nafs, and hifz al-māl are actualized in the practice of managing and implementing professional waqf in the Islamic boarding school environment. This study uses a qualitative approach with a descriptive-analytical research type. Data were collected through in-depth interviews with caretakers, waqf managers, and teachers as actors in professional waqf, as well as a documentary study of the internal regulations of the Islamic boarding school and literature related to waqf law. Data analysis was carried out through the stages of reduction, presentation, and drawing conclusions with verification of Islamic legal theory and the concept of maqasid al-Sharia as an analytical framework. The research results show that the implementation of professional waqf at Pondok Modern Darussalam Gontor for Girls reflects the principles of maqasid al-sharia through professional service oriented towards the welfare of the community, educational sustainability, and institutional independence. Although not yet formalized in positive law, this practice has strong sharia legitimacy as a contemporary waqf innovation in Islamic education.